2006
DOI: 10.1080/17453670610013303
|View full text |Cite
|
Sign up to set email alerts
|

Improved healing of ligament to bone with point fixation in rabbits

Abstract: Background Secure healing of soft tissue to bone is a prerequisite for many orthopedic operations. This healing can be achieved either by pressing the tissue against the bone (press fixation) or by suturing the soft tissue to the bone (point fixation).Experiments and findings We tested the hypothesis that point fixation of soft tissue to bone results in better mechanical properties than press fixation. 10 skeletally mature New Zealand White rabbits were operated on bilaterally at the knees. The medial collater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The outcome of instability surgery of the knee is supposedly dependent on the secure fixation and healing of soft tissue to bone. 17 Suture anchors were first reported as an easier device to obtain secure stability for use in soft tissue fixation to bone without constructing transosseous suture tunnels. 27 A previous biomechanical study reported that sMCL repair using suture anchors results in better healing compared with fixation with screws or staples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome of instability surgery of the knee is supposedly dependent on the secure fixation and healing of soft tissue to bone. 17 Suture anchors were first reported as an easier device to obtain secure stability for use in soft tissue fixation to bone without constructing transosseous suture tunnels. 27 A previous biomechanical study reported that sMCL repair using suture anchors results in better healing compared with fixation with screws or staples.…”
Section: Discussionmentioning
confidence: 99%
“…16 Khoschnau et al performed bilateral knee sMCL repair in a rabbit model and compared two types of plates: one with a flat undersurface and a second with a pegged undersurface. 17 In that study, mechanical testing of pegged anchors, which mimic suture anchors, was performed 4 weeks after surgery and showed better maximum load, linear stiffness, and energy uptake. Louati et al performed rotator cuff repair in a rabbit model and compared it with a contralateral native rotator cuff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation